2013
DOI: 10.1175/jhm-d-12-0191.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Flood Response: The June 2008 Flooding in Iowa

Abstract: The authors examine the hydroclimatology, hydrometeorology, and hydrology of extreme floods through analyses that center on the June 2008 flooding in Iowa. The most striking feature of the June 2008 flooding was the flood peak of the Cedar River at Cedar Rapids (3964 m 3 s 21 ), which was almost twice the previous maximum from a record of 110 years. The spatial extent of extreme flooding was exceptional, with more U.S. Geological Survey stream gauging stations reporting record flood peaks than in any other yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 57 publications
3
47
0
Order By: Relevance
“…The largest overlap in storm events, 69 %, is found for the two largest basins, 48.5 and 111.1 km 2 in size. This confirms results reported by Smith et al (2013b) and Zhou et al (2017), who also found markedly different rainfall climatologies for flood-producing storms in basins of different size.…”
Section: Discussionsupporting
confidence: 92%
“…The largest overlap in storm events, 69 %, is found for the two largest basins, 48.5 and 111.1 km 2 in size. This confirms results reported by Smith et al (2013b) and Zhou et al (2017), who also found markedly different rainfall climatologies for flood-producing storms in basins of different size.…”
Section: Discussionsupporting
confidence: 92%
“…The derivation of equation (13) is based on the hydraulic-geometric properties of channel networks [Mantilla, 2007]. We used spatially and temporally constant values for [Mutel, 2010;Smith et al, 2013] that occurred in the Iowa River basin using the Stage-IV radarrainfall product [Kitzmiller et al, 2013] as input. The results clearly show that the model can reasonably reproduce observed streamflow time series across a range of spatial scales and, as a result, the spatial scaling property of peak discharges.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Lavers and Villarini (2013) showed that more than 60% of the annual maximum floods during 1979-2011 period were associated with ARs over much of the central United States, with seven out of the ten largest floods associated with these storms. Moreover, ARs are the mechanisms responsible for some of the most devastating flooding events over this region in recent decades, including the floods of July 1993 (Dirmeyer and Kinter, 2009), June 2008 floods over eastern Iowa (Budikova et al, 2010;Smith et al, 2013), May 2010 flood in Nashville (Tennessee) and surrounding areas (Moore et al, 2012), and the flood of April 2013 over Chicago and eastern Iowa (Campos and Wang, 2015;Nayak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%